Fulfillment of Citizens' Rights and Obligations in National Defense and Security Based on a Study of the Holy Qur'an - Syamsuddin Tubingan; Ayu Nursanti; Nafisatun Nisa; Fitara Rahmania; Safaruddin Safaruddin (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Islam conceptualizes national defense as an expression of ukhuwah wathoniyah (national brotherhood) and a form of jihad fi sabilillah understood in a contextual and constructive way. This study aims to reinterpret the concept of defending the state within an Islamic framework to prevent the militarization of civilians, avoid the emergence of proxy military groups, and counter radical movements that misuse religion. Using a qualitative library research method based on classical and contemporary Islamic sources, the findings show that national defense can be understood as a form of contextual jihad that prioritizes peaceful contributions, civic responsibility, and social harmony rather than violence. The Qur’an provides the theological foundation by emphasizing justice, collective responsibility, and the protection of society. The study also highlights the importance of balancing citizens’ rights and obligations, where individuals not only receive protection but also actively contribute to national well-being. Therefore, a holistic approach to national defense is needed, integrating moral, social, and civic dimensions rather than focusing solely on military aspects. In conclusion, fulfilling the rights and obligations of national defense within Islamic values can create stability, security, and social justice, positioning it not only as a civic duty but also as a religious commitment toward achieving a prosperous and harmonious society (baldatun tayyibatun wa rabbun ghafur).